Education Level, Spiritual Intelligence, and Love of Money: Do They Correlate to Ethical Perception? - Istiariani, Irma; Arifah, Uliya (IAIN Surakarta, 2020)
The aim of this study is to shed some light on the impact of education level, spiritual intelligence, and love of money on ethical perception of accounting students which still remains unexplored thus far. The data were taken from 100 accounting students of several universities in Semarang Indonesia as the respondents. The data were further analyzed by employing PLS (Partian Least Square). The data analyses revealed several compelling results. First, there was no significant impact of education level on ethical perception of accounting students. Second, spiritual intelligence positively influenced the students’ ethical perception. Third, the education level was found to have no significant effect on love of money. Fourth, the spiritual intelligence negatively correlated to love of money. Fifth, the love of money did not provide a significant impact on students’ ethical perceptions. These results contribute to providing positive insights for academic stakeholders in solving ethical problems of accounting students who are going to be professional accountants and auditors. Additionally, the results of this study should be considered as ‘a wake-up call’ for accounting professionals to be more alert toward the threat of ethical violations that could potentially endanger their credibility.